THE FORMATION OF UKRAINIAN-LANGUAGE INFORMATICS TERMINOLOGY AND THE CONTRIBUTION OF M. I. ZHALDAK TO THE FORMATION OF THE SYSTEM OF PROFESSIONAL COMPETENCIES OF INFORMATICS TEACHERS (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2024)
The article presents and analyzes the problems of Ukrainian-language terminology in computer science. The issues of using terms in educational institutions and scientific publications are considered. Some terms are highlighted, and their use requires validity and pedagogical prudence. The views and position of Myroslav Ivanovych Zhaldak, Doctor of Pedagogical Sciences, full member of the National Academy of Pedagogical Sciences of Ukraine, on this topic are also highlighted. It is important to remember that creating Ukrainian-language computer science terminology is an important part of preserving Ukraine's cultural and linguistic heritage and contributes to increasing the accessibility and understanding of information technology among future computer science teachers. The study aims to analyze the formation of the concept of "information" and the views of Academician M. I. Zhaldak on the interpretation of the basic concepts of computer science, as well as on the problems of using Ukrainian-language terminology in scientific and pedagogical publications and educational literature on computer science, mathematics, and probability theory. The article describes Myroslav Ivanovych's significant contribution to the development of Ukrainian terminology in the field of computer science. The methodological basis of the study is the theoretical provisions of epistemology as a branch of philosophy where cognition is a process of reflecting reality that exists independently of consciousness and reality that can be recognized. Examples of incorrect statements and their corresponding Ukrainian literary language are given. The main aspects of the formation of Ukrainian-language computer terminology are outlined. The authors emphasized the need to present the content of scientific and pedagogical publications at the highest possible cultural and literary level to ensure a positive impact on students. This, in turn, will lead to the formation of their professional and general culture. Prospects for further research on this issue are also identified.
Keywords: M. I. Zhaldak; basic concepts of informatics; Ukrainian-language informatics terminology; professional training of informatics teachers; the culture of scientific and pedagogical publications; scientific approach to interpreting used terms